Exogenous expression of both matrix protein and glycoprotein facilitates infectious viral particle production of Borna disease virus 1 - Kanda, Takehiro; Sakai, Madoka; Makino, Akiko; Tomonaga, Keizo (Journal of general virology, 2022)
Borna disease virus 1 (BoDV-1) is a non-segmented, negative-strand RNA virus that is characterized by persistent infection in the nucleus and low production of progeny virions. This feature impedes not only the harvesting of infectious viral particles from infected cells but also the rescue of high titres of recombinant BoDV-1 (rBoDV-1) by reverse genetics. Here, we demonstrate that exogenous expression of both matrix protein (M) and glycoprotein (G), which are constituents of the viral lipid envelope, significantly facilitates the formation of infectious particles and propagation of BoDV-1 without affecting its viral RNA synthesis. Furthermore, simultaneous transfection of M and G expression plasmids with N, P and L helper plasmids by reverse genetics drastically enhances the rescue efficiency of rBoDV-1. On the other hand, we also show that overexpression of M induces obvious cytotoxicity similar to that of other Mononegaviruses. Together with our recent report showing that excess expression of G induces aberrant accumulation of immature G, a potential stimulator of the host innate immune response, it is conceivable that BoDV-1 may suppress excess expression of M and G to reduce the cytopathic effect, thereby leading to maintenance of persistent infection. Our results contribute not only to the establishment of an efficient method to recover high-titre BoDV-1 but also to understanding the unique mechanism of persistent BoDV-1 infection.